The Effects of Vitamin A Administration to Heifer and Pregnant Cow on the Changes of Hormonal and Body Weight - Sang-Rae Cho; Ui-Hyung Kim; Kuldeep Kumar; Seung-Hwan Lee; Myeung-Sik Lee; Hyeon-Shup Kim; Hyun-Jae Lee; Byoung-Chul Yang (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The objective of this study was to investigate the interrelationship of weight and hormonal changes through the administration of vitamin A to first time pregnant heifers. A total of 28 Korean heifers was used for this study. The heifers were divided into two groups - with vitamin A (n=14) and without vitamin A (control) (n=14) in the feed. Body weight increased in vitamin A treated heifers starting 9 months until 15 months. After pregnancy, vitamin A treated heifers were found to maintain higher body weights than the control group. Pre-pregnancy and post pregnancy progesterone levels were not different between the two groups. Serum estradiol levels of heifers at different growth stages showed relatively higher E2 levels than the control. Also, the control during pregnancy may show higher serum E2 levels than the vitamin A treated heifers. The growth phase serum estradiol levels in heifers may be relatively higher than the control. During pregnancy it showed a similar trend. Serum levels of vitamin A treated heifers did not differ from pregnant heifers at 5 months of age. However, after 5 months from conception until 8 months of treatment it showed a high level. Serum cholesterol in pregnant cows was higher in the control group than the treatment from beginning until the end of pregnancy. This is considered to be related to fetus development during pregnancy, as well as the mother's health.